Inhibition of peptide aggregation by means of enzymatic phosphorylation - Folmert, Kristin; Broncel, Malgorzata; v. Berlepsch, Hans; Ullrich, Christopher Hans; Siegert, Mary-Ann; Koksch, Beate (Beilstein Journal of Organic Chemistry, 2016)
As is the case in numerous natural processes, enzymatic phosphorylation can be used in the laboratory to influence the conformational populations of proteins. In nature, this information is used for signal transduction or energy transfer, but has also been shown to play an important role in many diseases like tauopathies or diabetes. With the goal of determining the effect of phosphorylation on amyloid fibril formation, we designed a model peptide which combines structural characteristics of α-helical coiled-coils and β-sheets in one sequence. This peptide undergoes a conformational transition from soluble structures into insoluble amyloid fibrils over time and under physiological conditions and contains a recognition motif for PKA (cAMP-dependent protein kinase) that enables enzymatic phosphorylation. We have analyzed the pathway of amyloid formation and the influence of enzymatic phosphorylation on the different states along the conformational transition from random-coil to β-sheet-rich oligomers to protofilaments and on to insoluble amyloid fibrils, and we found a remarkable directing effect from β-sheet-rich structures to unfolded structures in the initial growth phase, in which small oligomers and protofilaments prevail if the peptide is phosphorylated.
Keywords: aggregation; amyloids; peptide models; peptide phosphorylation; protein folding